Patient safety attitude and associated factors among nurses at Mansoura University Hospital: A cross sectional study - Shahenda A. Salih; Fadia A. Abdelkader Reshia; Wafa Abdein Humza Bashir; Ayat M. Omar; Shereen Ahmed Elwasefy (Elsevier, 2021)
Background: Patient safety is a high priority for the healthcare system worldwide. It is considered an indicator of the quality of care. Objective: This research assesses Egyptian nurses' attitude to patient safety and the factors that affect their attitude. Methods: A descriptive cross-sectional study. Data were collected using the staff information form and safety attitudes questionnaire. The study population was 350 nurses working in Mansoura University Hospital. Data were analyzed with frequency, percentage, mean, standard deviation, the Chi squire test, and ANOVA tests using SPSS. Results: None of the six domains of safety attitude - job satisfaction, teamwork, safety climate, the perception of management, stress recognition, and working conditions - were awarded a positive mean score above 75. 51.4% of the nurses had a neutral attitude toward patient safety. The main associated factors were educational level, experience, and attending training courses related to patient safety, which had a high effect on nurses' attitude (p-value < 0.01); age and marital status had a slight effect (p-value < 0.05), while gender and working unit had no significant relationship (p-value > 0.05). Conclusions: The attitude of nurses towards patient safety at Mansoura University Hospital was neutral, and strongly associated with educational level, years of experience, and attending training courses on patient safety. Therefore, it is strongly recommended to develop strategies towards an increasingly successful patient safety culture.